Analisis dan Evaluasi Kepatuhan Regulasi Atas Perencanaan dan Penganggaran APBKal di Desa Wonokromo, Pleret, Bantul - Athayarasya Anandrio; Kevin Auriga; Niken Cita Adi Laksmi; Nesya Arjumand Bano; Mukhlis Mukhlis (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This research aims to analyze and evaluate regulatory compliance in the planning and budgeting processes for the 2025 Anggaran Pendapatan dan Belanja Kalurahan (APBKal) in Wonokromo Sub-district, Pleret, Bantul. This study focuses on the phenomenon of significant budget revisions, particularly the reduction in allocations for community development and empowerment, which raises questions regarding the maturity of initial planning. Using a descriptive qualitative methodology, data is collected through document analysis on the official Village Information System website (wonokromo.id) as well as structured interviews with village officials and hamlet heads. The research results indicate that, in general, they have complied with procedural and administrative requirements. Regarding the revision of the Anggaran Pendapatan dan Belanja Kalurahan (APBKal), such activities represent active compliance with changes in district government regulations. Technical obstacles are identified in the timing of regulatory issuance, leading to budget adjustments that resulted in the finalization being rushed to meet the submission deadline. Meanwhile, formal community participation is fulfilled through the Village Development Planning Meeting (Musrenbangkal), but substantive participation remains hindered by residents’ busy schedules and the physical capacity of the village hall.